Pemanfaatan Sampah Organik menjadi Biowash oleh Kader PKK di Desa Tosari - Mohammad Nayaka Rama Yoga; Arif Dirwan Tanjung; Ahda Min Ichdal Umamy; Nailil Musyarrofah; Muhammad Zulfan Azka (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2024)
This research aims to evaluate the use of organic waste as biowash by PKK members in the village and to find factors that support and hinder the implementation of the program. This research was conducted qualitatively with a descriptive case study approach. Data was collected through participant observation, in-depth interviews, and document study. Research shows that the success of the program is greatly influenced by the level of knowledge of PKK cadres regarding organic waste management. While limited tools and lack of community awareness are obstacles that need to be overcome, an effective training process and support from the village government are the main supporting factors. This research found that this program not only benefits the environment, but can also improve the local economy. The results also show that this program can be used as a model for other villages.